DISPARITY IN JUDGES’ DECISIONS IN CRIMINAL ACTS OF DOMESTIC NEGLECT (CASE STUDY OF DECISION NUMBER 575/PID PID.SUS/2017/PN KPN AND DECISION NUMBER 95/PID.SUS/2024/PN TIM) - Puti Almas; Yuliati; Sudarsono (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Disparity can be associated with the existence of differences or inconsistencies in the application of punishment in court decisions for similar or comparable cases. Disparity may be defined as unjustified differences in legal treatment, either in the type or severity of punishment, for cases with similar characteristics. This research aims to examine and analyze the legal considerations used by the panel of judges that led to the occurrence of disparities in decisions for the crime of domestic neglect, based on Decision Number 575/Pid.Sus/2017/PN Kpn and Decision Number 95/Pid.Sus/2024/PN Tim. It also aims to assess whether the two decisions have fulfilled the principles of justice, utility, and legal certainty. The research method used is normative juridical, employing normative legal, conceptual, and case approaches. The legal research data consist of secondary data, including primary, secondary, and tertiary legal materials. The findings of this thesis indicate that there is a disparity between Decision Number 575/Pid.Sus/2017/PN Kpn and Decision Number 95/Pid.Sus/2024/PN Tim. This is because the conditions of “disparity in the same criminal act,” “disparity in sentencing by different judicial panels for the same crime,” “disparity in sentencing by the same judicial panel,” and “disparity in crimes of equal seriousness” have been met. Additionally, it was found that Decision Number 575/Pid.Sus/2017/PN Kpn satisfies the principles of justice, legal utility, and legal certainty. In contrast, Decision Number 95/Pid.Sus/2024/PN Tim only ensures legal certainty for the interested party, failing to uphold the principles of justice and utility, particularly in relation to the victim.